Pengaturan Pidana Pengawasan dan Pidana Kerja Sosial dalam Rancangan KUHP sebagai Upaya Menerapkan Daad-Dader Strafrecht - Diah Ratu Sari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
There are new regulation of punishment in the draft of criminal code: punishment of supervision and social work. These two punishments are not imprisonment. We hope that without imprisonment, someone who is punished guilty can be avoided from bad effect in the prison. The problems in this research are how is the formulation policy about punishment of supervision and social work in the draft of criminal code and what is the basic philosophy of punishment of supervision and social work in the draft of criminal code. This research wants to know and analyze the formulation policy about punishment of supervision and social work in the draft of criminal code and the basic philosophy of punishment of supervision and social work in the draft of criminal code. This study is a normative research. The conclusion of the research is that the formulation policy about punishment of supervision and social work in the draft of criminal code is a consequency of daad-daderstraftrecht which as far as tries to develope alternative for imprisonment because the regulation is not oriented only to the action but also oriented to the offender. The basic philosophy of punishment of supervision and social work regulated in the draft of criminal code is to avoid bad stigma as a prisoner, to reduced over capacity of prisoners in the prison, and the money that is given as a social worker may be given to his family. Keywords: punishment of supervision, social work, daad-daderstrafrecht AbstrakDalam Rancangan KUHP diatur jenis pidana pokok baru yaitu pidana pengawasan dan pidana kerja sosial. Dua jenis pidana ini bukan pidana perampasan kemerdekaan. Tanpa menjalani pidana perampasan kemerdekaan diharapkan terpidana terhindar dari akibat buruk jika menjalani hukuman di Lembaga pemasyarakatan. Permasalahan yang diteliti adalah tentang kebijakan formulasi pengaturan pidana pengawasan dan pidana kerja sosial dalam Rancangan KUHP dan tentang dasar filosofi pengaturan pidana pengawasan dan pidana kerja sosial dalam Rancangan KUHP. Penelitian ini bertujuan mengetahui dan menganalisis kebijakan formulasi pengaturan pidana pengawasan dan pidana kerja sosial dalam Rancangan KUHP dan dasar filosofi pengaturan pidana pengawasan dan pidana kerja sosial dalam Rancangan KUHP. Penelitian ini menggunakan metode penelitian normatif. Kesimpulan dari penelitian ini adalah bahwa kebijakan formulasi pencantuman jenis pidana pengawasan dan pidana kerja sosial merupakan konsekuensi diterimanya hukum pidana yang bersifat daad-daderstrafrecht yang sejauh mungkin berusaha untuk mengembangkan alternatif pidana kemerdekaan, karena ketentuan dalam undang-undang ini bukan hanya berorientasi pada perbuatan tetapi juga berorientasi pada pelaku. Dasar filosofi pengaturan pidana pokok dalam Rancangan KUHP khususnya pidana pengawasan dan pidana kerja sosial adalah menghindarkan stigma buruk sebagai mantan terpidana jika menjalani pidana penjara, mengurangi over capacity di lembaga pemasyarakatan dan uang yang dihasilkan dari menjalani pidana kerja sosial dapat membantu nafkah bagi keluarga terpidana.Kata kunci: Pidana Pengawasan; Pidana Kerja Sosial; Daad-Dader Strafrecht